The Influence of Sociodrama Method in Improving Creativity and Motivation to Learn in Early Childhood - Jaslina; Susanti, Debie (Kirana Publisher (KNPub), 2024)
This study aims to analyze the effect of the sociodrama method on creativity and learning motivation in early childhood in group B kindergarten in Banda Aceh City. The research method used is a quantitative experiment with a quasi-experiment design. The results showed that the sociodrama method significantly increased children's creativity and learning motivation. Through the dramatization process, children are invited to play an active role in learning activities, which stimulates their creativity and interest in learning. The test results show that the sociodrama method is able to provide a more meaningful and interactive learning experience for children, which contributes to the development of their creativity. Early childhood learning motivation stimulated by sociodrama can be seen from increased curiosity, enthusiasm, and perseverance in the learning process. The result of statistical analysis shows that there is a significant difference in the level of creativity and learning motivation of children using the sociodrama method compared to conventional learning methods. In conclusion, the sociodrama method is effective in improving both aspects, with learning motivation showing a more dominant influence than creativity. This finding implies that teachers and educators need to apply the sociodrama method more widely in early childhood learning activities to create a more dynamic and creative learning environment